SERVICE ANALYSIS AND BUSINESS MANAGEMENT OF MUHAMMADIYAH SURYA MANDIRI SHARIA PRODUCER COOPERATION - Millisa, Cut; Pratiwi, Putri; Adelina, Dian; Rifaldy Rizky, Muhammad; Sinta, Irada (RADJA PUBLIKA, 2023)
Sharia cooperative is a form of cooperative that has principles, goals, and activities based on the achievement of Islamic sharia, namely the Koran and Assunah. In general, this cooperative is a cooperative business entity that carries out its business activities based on sharia principles. And Cooperative services to members are services provided by Cooperatives in advancing the business of its members. Therefore, some cooperatives provide and improve services to the businesses of their members very well. The management of this sharia cooperative business is to open outlets that sell various needs ranging from food, school necessities, and various daily needs. This cooperative has also opened several businesses such as savings and loans, and benevolent loans, which are loans that do not take advantage. It is from these businesses that this Islamic cooperative earns income. So it is urgent to examine the level of service and management of the cooperative. The methods used in this cooperative This research is a purposive sampling research method, namely the method of determining research locations that are carried out deliberately based on certain considerations.